ANALYTICAL STUDY ON THE USE OF BIOSECURITY SYSTEMS IN CHICKEN FARMING TO PREVENT DISEASE - Zulkifli, Zulkifli (Antis-Publisher, 2025)
Objective: This research aims to analyze the implementation of biosecurity systems in chicken farms and provide strategies to improve their effectiveness. The goal is to support a safer, more productive, and sustainable farming ecosystem while reducing the risk of disease outbreaks that could threaten the livestock sector. Method: A qualitative approach was used with library research or literature study as the primary method. Data sources were collected from scientific journal articles and research reports to gain a comprehensive understanding of biosecurity practices in chicken farming. Results: The study found that the application of biosecurity systems in chicken farms varies based on farm size, with large-scale farms demonstrating better implementation due to greater resources, knowledge, and technical support. Effective strategies for improving biosecurity include training programs for farmers, providing adequate facilities, financial assistance, and supervision. However, small-scale farms face significant challenges, including limited funds, lack of knowledge, inadequate facilities, and resistance to change, which hinder optimal biosecurity implementation. Novelty: This study highlights the importance of a collaborative approach involving farmers, governments, and stakeholders to improve biosecurity practices. It also emphasizes the need for tailored strategies that address the unique challenges faced by small-scale farms, offering actionable solutions to enhance sustainability and disease prevention in the poultry industry.